2005
DOI: 10.1017/s1350482705001556
|View full text |Cite
|
Sign up to set email alerts
|

Standards‐based data interoperability in the climate sciences

Abstract: Emerging developments in geographic information

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…For instance, the AODC JF partners found that it was difficult to deal with the time dimension in OGC Web Map services. Woolf et al (2005) also encountered this problem and reported other difficulties including the lack of appropriate support for using a range of vertical coordinate systems in the WMS specification, a specification that was essentially designed for 2-dimesional mapping.…”
Section: Observations From Australia's Marine Sdi Activitiesmentioning
confidence: 99%
“…For instance, the AODC JF partners found that it was difficult to deal with the time dimension in OGC Web Map services. Woolf et al (2005) also encountered this problem and reported other difficulties including the lack of appropriate support for using a range of vertical coordinate systems in the WMS specification, a specification that was essentially designed for 2-dimesional mapping.…”
Section: Observations From Australia's Marine Sdi Activitiesmentioning
confidence: 99%
“…An emerging series of international standards for geospatial data, metadata and services provides a timely basis for meeting the data integration requirements outlined above (Woolf et al, 2005b). The series (comprising some 40 standards) is being developed by Technical Committee 211 (Geographic Information and Geomatics) of the International Organisation for Standardisation (ISO) 1 .…”
Section: Geospatial Data Standardsmentioning
confidence: 99%